Climate-smart agricultural practices among rural farmers in Masvingo district of Zimbabwe: perspectives on the mitigation strategies to drought and water scarcity for improved crop production - Mpala, Thandiwe Annastacia; Simatele, Mulala Danny (Frontiers in Sustainable Food Systems, 2024)
Climate change is one of the most significant challenges faced by many rural farmers in sub-Saharan Africa, as the majority of agricultural practices are rain-fed dependent. Many of these rural farmers are considered small-scale farmers with limited access to financial assets, agricultural equipment, and inputs. With a rapidly changing climate and limited access to agricultural resources, many rural farmers in Zimbabwe have found it extremely difficult to engage in meaningful crop production activities and secure their livelihoods and incomes. Despite this situation, many rural farmers in Zimbabwe, particularly in Masvingo District, are not passive actors but are actively involved in articulating various agricultural practices to build their adaptive capacity and resilience against climate variability and change. Among such initiatives is the adoption of agricultural activities and practices, which include optimal water resource utilisation, early maturing seed use, soil, and water conservation techniques (SWM), and nutrient management techniques (NMT), including cost-effective labour and post-harvest storage facilities. Using methods inspired by the tradition of participatory research, this paper examines and discusses the comprehensiveness of these techniques and approaches to improving crop production and building vulnerable households' adaptive capacity and resilience against extreme weather events. These themes have been discussed within the broader framework of sustainable goals, particularly goals 1 and 2.